Alternative conversations : queer children and re-negotiating identities. - Yeo, Cindy Wen Ting. (2013)
The quintessential image of the queer child in literature is an iconic one: young Lolita in a swimsuit, peering seductively at Humbert Humbert. What is problematic about this image is its suggestion that children can be the more powerful in a relationship between unequals. Significantly, her story is told as a legal statement by Humbert, which places her as an object to be eroticized and/or condemned. What I am interested in are representations of children who narrate their stories despite their voices being subsumed by the dominant discourses of their cultures. This essay will re-examine the figure of the queer child through three controversial novels: Arundhati Roy’s The God of Small Things; Lilian Lee’s Farewell My Concubine; and Alice Walker’s The Colour Purple. These texts problematize the relationship between children and language, particularly children from oppressive political and cultural backgrounds where their rights are not protected by legal structures like Lolita’s are. These three texts, I argue, deploy new images of children queered not only by their sexual presentations but also by social forces leading them toward alternative ways of narrating themselves into legal discourse.